Mitochondrial disease associated with the T8993G mutation of the mitochondrial ATPase 6 gene: a clinical, biochemical, and molecular study in six families. Issue 1 (1st July 1997) - Uziel, G; Moroni, I; Lamantea, E; Fratta, G M; Ciceri, E; Carrara, F; Zeviani, M
Abstract : AIM: To contribute to the establishment of a rational clinical, neuroradiological, and molecular approach to neurogenic muscle weakness, ataxia, and retinitis pigmentosa (NARP) and maternally inherited Leigh's syndrome (MILS). METHODS AND RESULTS: The T8993G mutation in the mitochondrial genome was found in several maternal members of six pedigrees, whose clinical status ranged from no symptoms to severe infantile subacute necrotising encephalomyelopathy (Leigh's disease). In one case a MELAS-like syndrome was documented both clinically and neuroradiologically. Relevant genetic features of the series were anticipation of symptoms through subsequent generations, and the presence of several cases in whom the mutation apparently occurred recently or was new. A uniform distribution of the mutation in many tissues was shown in one patient subjected to necropsy. In general, a good correlation was found between clinical severity and mutation heteroplasmy in readily accessible tissues, such as lymphocytes or fibroblasts. By contrast, a consistent reduction of the mitochondrial ATPase activity, to about half of the normal values, was found in most of the clinically affected cases, irrespective of the amount of mutant mitochondrial DNA. CONCLUSIONS: Although the measurement of ATP hydrolysis in cultured fibroblasts was a reliable, and sometimes instrumental, means to identify T8993G positive patients, the relation between the mutation and the oxidative phosphorylation defect is probably very complex, and its understanding requires more complex biochemical analysis.